Application of Substantive and Formal Legal Rules Related to Approval to Avoid Double Taxation as an Effort to Maximize Tax Revenue - Damayanti, Ratih (Jurnal Indonesia Sosial Sains, 2025)
Tax revenue is the main source of state revenue, but disputes often arise related to the application of Double Taxation Avoidance Agreements (DTAs). These disputes generally revolve around the fulfillment of administrative requirements, especially the inclusion of a Domicile Certificate (SKD). This research aims to analyze the application of material and formal legal principles in two Tax Court decisions, namely PUT-001293.35/2020/PP/MXVIIIA Year 2022 and PUT-004868.13/2021/PP/MXIIIB Year 2022, as well as the implications for legal certainty and taxpayer protection. The research uses normative juridical method with statutory, case, and conceptual approaches. Data is obtained from literature studies in the form of laws and regulations and legal doctrines. The results show that decisions that prioritize material legal principles provide substantive justice but have the potential to weaken the application of tax regulations. Conversely, decisions that prioritize formal legal principles provide legal certainty by emphasizing the importance of fulfilling administrative requirements. The conclusion of this research emphasizes the need for a balance between substantive justice and legal certainty in the application of P3B. Implementing regulations, such as PER-25/PJ/2018, are important instruments to ensure P3B is used appropriately and prevent misuse, thus supporting the optimization of tax revenue